The Concept of Hedging Instrument Forward In Islamic Economic Perspective - Bambang Hidayat; Ayu Rahayu Nurhalizah; Andriani Samsuri; Eka Nurjannah (Universitas Islam Lamongan, 2022)
This research aims at explaining more in-depth about Islamic hedging related to the problem of muwa’adah status in Islamic hedging. The use of muwa’adah as an Islamic hedging instrument which promises to carry out transactions in the future, actually still becomes a subject of debate since there are some different opinions about whether or not it is permissible to carry out the concept of muwa’adah in a transaction. This research is descriptive qualitative research and uses qualitative data analysis, by conducting a direct analysis of the hedging scheme through the process of data reduction, data display, and verification. The results of this study reveal that in sharia hedging, swap and forward contracts should not be used, because swaps and forwards contain elements of usury. While the option contract contains speculation (maysir). If the forbidden aspects (haram) in ‘forward’ and ‘swap’ instruments are analyzed, generating al-sharf al-ajil and maysir (khathar/speculation), then the alternatives are 1) forward agreement by way of a price-fixing agreement; 2) bay’ al-iltizam; 3) bay’ al-‘urbun; and 4) al-bay’ bi al-shart.